Candidemia Candida albicans clusters have higher tendency to form biofilms than singleton genotypes. (5th February 2020) - Díaz-García, Judith; Arendrup, Maiken C; Cantón, Rafael; García-Rodríguez, Julio; Gómez, Ana; Gómez, Elia; Orden, Beatriz; Parisi, Gabriella; Pemán, Javier; Posteraro, Brunella; Sanguinetti, Maurizio; Da Matta, Daniel Archimedes; et al.
Abstract: The capacity of Candida spp. to form biofilms allows them to attach either to living or inert surfaces, promoting their persistence in hospital environments. In a previous study, we reported strain-to-strain variations in Candida spp. biofilm development, suggesting that some genotypes may be greater biofilm formers than others. In this study, we hypothesize that isolates pertaining to clusters may be found more frequently in the environment due to their ability to form biofilms compared to singleton genotypes. Two hundred and thirty-nine Candida spp. isolates (78 clusters) from candidemia patients admitted to 16 hospitals located in different cities and countries—and the same number of singleton genotypes used as controls—were tested in terms of biofilm formation using the crystal violet and the XTT reduction assays. Candida albicans clusters showed higher biofilm formation in comparison to singleton genotypes ( P  < .01). The biofilms formed by intra-hospital C. albicans clusters showed higher metabolic activity ( P  < .05). Furthermore, marked variability was found among species and type of cluster. We observed that the higher the number of isolates, the higher the variability of biofilm production by isolates within the cluster, suggesting that the production of biofilm by isolates of the same genotype is quite diverse and does not depend on the type of cluster studied. In conclusion, candidemia Candida spp. clusters—particularly in the case of C. albicans —show significantly more biomass production and metabolic activity than singleton genotypes.